1976
DOI: 10.1111/j.1365-2141.1976.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis in Haemophilia: A Double‐blind Controlled Trial

Abstract: A double-blind controlled trial of prophylactic factor VIII therapy has been carried out on nine severe haemophiliacs at the Lord Mayor Treloar College. Infusions were given once weekly and calculated to give a post-infusion plasma concentration of at least 0.25 I.U./ml of factor VIII. This regime reduced the overall bleeding frequency by 15%. The bleeding frequency in the first 3 days post-infusion was reduced by 66%. A moderate overall reduction in morbidity was also achieved. It is calculated that to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
2

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 11 publications
2
64
0
2
Order By: Relevance
“…In prophylactic treatment, the patient receives clotting factor product infusions two (hemophilia B) or three (hemophilia A) times a week, aimed at maintaining a clotting factor level of more than 1% of the normal value (0.01 lU/ml) at all times. Since joint damage is absent or mild in patients with moderate or mild hemophilia, it has been suggested that prophylactic therapy started at an early age could prevent joint damage altogether [2,8,91,95,137]. In prophylactic therapy, bleedings probably are not truly prevented, but arrested at the earliest, subclinical phase.…”
Section: Prophylactic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In prophylactic treatment, the patient receives clotting factor product infusions two (hemophilia B) or three (hemophilia A) times a week, aimed at maintaining a clotting factor level of more than 1% of the normal value (0.01 lU/ml) at all times. Since joint damage is absent or mild in patients with moderate or mild hemophilia, it has been suggested that prophylactic therapy started at an early age could prevent joint damage altogether [2,8,91,95,137]. In prophylactic therapy, bleedings probably are not truly prevented, but arrested at the earliest, subclinical phase.…”
Section: Prophylactic Treatmentmentioning
confidence: 99%
“…In prophylactic therapy, bleedings probably are not truly prevented, but arrested at the earliest, subclinical phase. It has been shown that prophylaxis reduces the number of manifest bleedings by äs much äs 60% [8,9].…”
Section: Prophylactic Treatmentmentioning
confidence: 99%
“…This may have been due in part to the several sources of potential observer and patient bias inherent in any attempt to evaulate such a regime. A double-blind controlled trial of prophylactic treatment has been carried out at the Treloar Haemophilia Centre (Aronstam et al, 1976) where personnel facilities and geographic considerations permit the separation of clinical management and trial administration. The weekly administration of factor VIII-containing material calculated to raise the factor VIII level to 0-25 IU/ml (25% of average normal) reduced the overall bleeding frequency in nine severe haemophiliacs by 15%.…”
mentioning
confidence: 99%
“…Although the cost of prophylaxis is very high, cost benefit study showed that the ultimate expenses may not be greater than those for treatment on demand 41 . However, universal implementation of primary prophylaxis in children is challenging in developing countries where only resource for minimal on demand treatment is available.…”
Section: Intermittent (Periodic) Prophylaxismentioning
confidence: 99%
“…Prophylactic infusion of factor concentrate of FVIII and FIX is widely accepted as gold standard treatment in children with severe hemophilia 41 . Prophylaxis prevents bleeding and joint destruction and should be the goal to preserve normal musculoskeletal function 42,43 .…”
Section: Immune Tolerance Induction (Iti)mentioning
confidence: 99%